Deportees and crime in Barbados - Griffin, Clifford E. (2000)
Seeks to shed light on the impact of criminal deportees on Caribbean societies by focusing on Barbados. Questions whether it is the case that criminal deportees are introducing sophisticated criminal activities to Barbados. Draws upon three sets of data to answer this question.